The great race - Haq, Roohi (Karachi : Paramount books, 2015)
Traditionally, teaching values and social skills has been left to parents; it is increasingly becoming incumbent on teachers to teach these skills. As children grow up they need to learn many lessons about relationships personal integrity, courage and compassion and stories provide the context and link to real life for students to learn these values.
Keywords: English - fiction; Children - stories